The Zest for Patient Empowerment - Rangeel Singh Raina; Vijay Thawani (Journal of Clinical and Diagnostic Research, 2016)
Patient Empowerment (PE) can be considered as an active and self-determining role of patient than a passive recipient of health related services. It encourages the provider–patient relationship to blossom and helps in clearing patients’ doubts, confusion and fears to bring in clarity, relief and assurance. For the active involvement of the patient's in own health management they need to be awakened, motivated, educated and enlightened to enable them to exercise their rights. Active patient involvement in the decision-making achieves favourable health outcome. In an empowerment based approach, the focus is not on defining a particular type of behaviour, but on how the behaviour is defined as a goal to be achieved by a particular individual. As a result of their empowerment process, the patients can better self-manage their illness and their lives. Thus empowerment of the patients will positively help medical uprising of the community by creating an educated, health aware, informed and health conscious mass.